2022
DOI: 10.3389/fpsyg.2022.947296
|View full text |Cite|
|
Sign up to set email alerts
|

Study protocol of a randomized controlled trial of motivational interviewing-based intervention to improve adherence to continuous positive airway pressure in patients with obstructive sleep apnea syndrome: The MotivAir study

Abstract: ObjectiveThis study aims to evaluate the effectiveness of the MotivAir program—a phone-based intervention based on Motivational Interviewing (MI) principles and techniques—in enhancing adherence to Continuous Positive Airway Pressure (CPAP) therapy among patients with Obstructive Sleep Apnea Syndrome (OSAS).MethodsA multicenter randomized controlled trial (RCT) design with random allocation at the level of the individual will be conducted to compare the impact of the experimental program (usual care plus MI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Moreover, as also demonstrated in previous studies (Hagedoorn et al, 2000;Rapelli et al, 2020Rapelli et al, , 2021b, receiving support (both emotional and in dealing with technical issues of the machine) from the partner leads to improved adherence and clinical outcomes in patients with OSAS using CPAP. On the contrary, adherence appears scant among patients living alone (Luyster et al, 2016;Rapelli et al, 2022). Indeed-as shown in other research (Sawyer et al, 2010)-unmarried patients in this study reported lower perceived ability to manage the device and fewer positive experiences with the CPAP compared to their married counterparts.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Moreover, as also demonstrated in previous studies (Hagedoorn et al, 2000;Rapelli et al, 2020Rapelli et al, , 2021b, receiving support (both emotional and in dealing with technical issues of the machine) from the partner leads to improved adherence and clinical outcomes in patients with OSAS using CPAP. On the contrary, adherence appears scant among patients living alone (Luyster et al, 2016;Rapelli et al, 2022). Indeed-as shown in other research (Sawyer et al, 2010)-unmarried patients in this study reported lower perceived ability to manage the device and fewer positive experiences with the CPAP compared to their married counterparts.…”
Section: Discussionsupporting
confidence: 44%
“…The results presented in this article are from the preliminary phase of a larger project to develop and implement a telephone-based behavioral and motivational intervention to improve adherence to recommended OSAS treatment (Rapelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies should be valuable in increasing understanding of how MI intervention increases CPAP adherence and the Apnea-Hypopnea Index, as well as secondary outcomes, such as motivation, perceived competence, QoL, and sleepiness at various intervals (1-, 3-, and 6-months). 56 …”
Section: Sleepmentioning
confidence: 99%
“…A recent investigation aimed at assessing the societal and economic burden of OSA in Italy, estimated that about 56% of the adult population (from 15 to 74 years of age) are affected by OSA but only 4% received a diagnosis, and only 2% were treated [1,20,21]. Since this condition is constantly rising along with the global increase in obesity, it requires appropriate consideration in prevention programs [16].…”
Section: Introductionmentioning
confidence: 99%